Spatial Ecology of Sub-Adult Green Turtles in Coastal Waters of the Turks and Caicos Islands: Implications for Conservation Management - Doherty, Philip D.; Broderick, Annette Cameron; Godley, Brendan John; Hart, K. A.; Phillips, Q.; Sanghera, A.; Stringell, Thomas B.; Walker, J. T.; Richardson, Peter Bradley (Frontiers in Marine Science, 2020)
Marine turtles are of conservation concern throughout their range, with past population declines largely due to exploitation through both legal and illegal take, and incidental capture in fisheries. Whilst much research effort has been focussed on nesting beaches and elaborating migratory corridors, these species spend the vast majority of their life-cycle in foraging grounds, which are, in some species, quite discrete. To understand and manage these populations, empirical data are needed on distribution, space-use, and habitats in order to best inform design of protective measures. Here we describe space-use, occupancy, and wide-ranging movements derived from conventional flipper tagging and satellite tracking of sub-adult green turtles (Chelonia mydas) within the coastal waters of the Turks and Caicos Islands (TCI; 2011-2017). Sixteen individual turtles of between 63 and 81 cm curved carapace length (CCL) were satellite tracked for a mean 226 days (range: 38-496). Analyses of both satellite tracking and conventional flipper tagging data revealed extended periods of occupancy in the shallow coastal waters within a RAMSAR protected area that includes seagrass beds and algae-rich tidal creeks. Satellite tracking also revealed wide-ranging movements, with four of 16 turtles exhibiting directed movements away (displaced >450 km) from TCI waters travelling through nine geo-political zones within the Caribbean-Atlantic basin, as well as on the High Seas. One turtle travelled to the Central American coast before settling on inshore habitat in Colombia’s waters for 162 days before transmission ceased, indicating ontogenetic dispersal to a distant foraging habitat. These data highlight connectivity throughout the region, displaying key linkages between countries that have previously only been linked by genetic evidence. This study also provides evidence of the importance of the Turks and Caicos Islands marine protected area network and importance of effective management of the sea turtle fishery for regional green turtle populations.